Relationship between the Lifestyle and Mental Health of Medical Students of UCMS, Bhairahawa: A Cross-Sectional Study - Poudyal, Sreya; Gautam, Narayan; Pathak, Laxmi; Yadav, Pooja; Bashyal, Srijana; Chochange, Sonam; Joshi, Gayatri; Dhakal, Nirmala; Bhandari, Anish; Shrees, Prakriti Thapa; Jha, Goody; Shrestha, Sujata (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Medical students suffered from high level of stress during their studies and this percentage has been increasing. This study was conducted to ﬁnd out association between lifestyle and mental health of MBBS and BDS students to encourage effective intervention to manage the stress. MATERIAL AND METHODS A cross sectional study was conducted at Universal College of medical sciences, Bhairahawa comprising both MBBS and BDS students from ﬁrst to ﬁnal years by written questionnaire using stress assessing tools. RESULTS Out of 202 students, 85.1% participants experienced stress of which 73.2% went through moderate stress while 11.9% with high stress. MBBS students were found to be more stressed than that BDS which was 59.4%. While concerning global PSQI, 57.9% complained for disturbed sleep. A signiﬁcant association of stress was found with poor study ability as 89.2% experienced difﬁculty in coping up with study. Although more than half of students are physically active, the perceived stress score was seen still higher. A positive correlation was seen between study pattern with global PSQI (r =0.347, p= 0.001) and PSS (r =0.519, p=0.001). CONCLUSION Sleeping pattern, physical activity, substance abuse and nutrition affect mental status. Hence, interventions should be done considering all dimensions to avoid further fatal consequences.